DO WE REALLY NEED COMPUTERS IN CLASSROOM INSTRUCTIONS (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The Quality of education depends to a great extent on thequality of teachers. It is a known fact that quality teachers optfor an innovation in their teaching aspect through integratingtechnology in the classroom instruction to give the best tostudents. Since technology is a powerful tool for problem –solving, conceptual development and critical thinking help tomake the learning process much easier for the students. To beeffective in the classroom instruction, teachers should acquirethe knowledge and skills to use the new challenges inpromoting innovative teaching strategies that are studentcentered,collaborative, engaging, authentic, self-directed andbased on the development of higher order thinking skills withrespect to handling classes for students which aim to achievehigh academic standards.Today learning is approached as a constructive, self-regulated,and cooperative to meet the individual difference andtechnology-oriented process. In these approaches a strongemphasis is placed on the learner as an active agent in theknowledge acquisition process. This view on learning andinstruction is in contrast with the ‗Objectivistic‘ viewpoint inwhich information provided by, for example, a teacher ismore or less directly transferred to the learner. In theconstructive viewpoint, the teacher plays a more facilitativerole, supporting learners in a self-directed, constructivelearning process. Developments in the objectivistic traditionwere encouraged by the availability of computer-basedlearning environments that were in line with this approach,such as programmed instruction, tutorials, drill-and-practiceprograms. Also within the constructivist approach we findcomputer-learning environments that help to advancedevelopments